Comparing, Contrasting, and Integrating Dissemination and Implementation Outcomes Included in the RE-AIM and Implementation Outcomes Frameworks - Reilly, Kathryn Louise; Kennedy, Sarah; Porter, Gwenndolyn; Estabrooks, Paul (Frontiers in Public Health, 2020)
As the field of dissemination and implementation science matures, there are a myriad of outcomes, identified in numerous frameworks, that can be considered across individual, organizational, and population levels. This can lead to difficulty in summarizing literature, comparing across studies, and advancing translational science. This manuscript sought to (1) compare, contrast, and integrate the outcomes included in the RE-AIM and Implementation Outcomes Frameworks (IOF) and (2) expand RE-AIM indicators to include relevant IOF dissemination and implementation outcomes. Cross tabular comparisons were made between the constitutive definitions of each construct, across frameworks, to reconcile apparent discrepancies between approaches and to distinguish between implementation outcomes and implementation antecedents. A great deal of consistency was identified across approaches, including adoption (the intention, initial decision, or action to employ an evidence-based intervention), fidelity/implementation (the degree to which an intervention was delivered as intended), organizational maintenance/sustainability (extent to which a newly implemented treatment is maintained or institutionalized), and cost. The IOF construct of penetration was defined as a higher-order construct that may encompass the reach, adoption, and organizational maintenance outcomes within RE-AIM. Within the IOF approach acceptability, appropriateness, and feasibility did not match constitutive definitions of dissemination or implementation but rather reflected theoretical antecedents of implementation outcomes. Integration of the IOF approach across RE-AIM indicators was successfully achieved by expanding the operational definitions of RE-AIM to include antecedents to reach, adoption, implementation, and organizational maintenance. Additional combined metrics were also introduced including penetration, individual level utility, service provider utility, organizational utility, and systemic utility. The expanded RE-AIM indicators move beyond the current approaches described within both the RE-AIM framework and IOF and provides additional planning and evaluation targets that can contribute to the scientific field and increase the translation of evidence into practice.